(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Critical thinking is an essential skill that helps children analyze information, solve problems, and make informed decisions. As the world becomes increasingly complex, fostering critical thinking from an early age is crucial for lifelong success. This article explores various strategies parents and educators can use to nurture these skills in children, including inquiry-based learning, problem-solving activities, and media literacy. It also examines the role of technology in shaping children’s cognitive abilities. By understanding and implementing these approaches, we can better equip children with the critical thinking skills needed for academic, personal, and professional growth.